Dynamics of Salmonella inoculated during rearing of black soldier fly larvae (Hermetia illucens). (November 2021) - De Smet, J.; Vandeweyer, D.; Van Moll, L.; Lachi, D.; Van Campenhout, L.
Graphical abstract: Highlights: BSFL does not show a reducing effect on Salmonella counts on chicken feed. The background microbiota is an important factor during inoculation experiments. Airborne transmission is possible in laboratory conditions during insect rearing. Salmonella free substrate is recommended to avoid the pathogen entry in rearing. Abstract: The black soldier fly is currently the most produced edible insect on industrial scale, with its larval stage being processed into animal feed as the main application. As this insect species enters the feed and food chain, good hygiene and monitoring practices are needed to avoid the entrance of foodborne pathogens via the larvae. However, insufficient data on the risk of such introductions via industrial larvae production are available. To address this gap, a range of rearing trials were conducted in which the substrate, chicken feed, was inoculated with different levels of Salmonella and in which total viable counts and Salmonella counts were determined during the following days. The outgrowth of Salmonella was slower in those experiments with a lower initial contamination level than in experiments with a higher level. No significant reducing effect originating from the larvae on the substrate Salmonella counts was observed, in contrast to previous studies using other substrates. Our study also revealed that airborne transmission of Salmonella is possible under rearing conditions corresponding to those applied at industrial production sites. Based on our results, we recommend insect producers to use substrate ingredients free of Salmonella, and not to count on the antimicrobial activities that BSFL may exert in some situations towards food pathogens. More inoculation studies using other Salmonella serotypes, other zoonotic bacteria, other substrates, larvae of other ages and including variations on rearing protocols are needed in order to obtain a general view on the dynamics of food pathogens in this insect species and to support comprehensive risk assessments.